Puppets and Population - Baird, Bil.; World Education, Inc., New York, NY. ([Washington, D.C.] : New York : Distributed by ERIC Clearinghouse, World Education, 1972)
This document focuses on the use of puppets for educating the illiterate populations of the world in food production and family planning. It is presented as one practical and effective tool for the adult educator and literacy worker. When used as part of a total program of functional literacy for family life planning, it can help young adults gain a wider understanding of population problems and of the options available to them if they wish to limit the size of their families. The play, "Small Family, Happy Family," can be translated into any language. (CK)
Educational level discussed: Adult Basic Education.
Educational level discussed: Adult Education.
Microfiche.
Keywords: Adult Basic Education; Adult Education; Contraception; Developing Nations; Educational Programs; Family Life; Family Planning; Food; Functional Literacy; Instructional Materials; Puppetry; Teaching Methods; Theater Arts